A place to grow; group accommodation for children with autism spectrum disorder - Edgren, Johanna (My University, 2025)
Children with autism spectrum disorder (ASD) live in group accommodations for various reasons when it is deemed to be the best solution for them and their needs. The home environment is especially important for these children because of their tendency to be hyperor hypo-sensitive to sensory impressions and the need for a safe and structured environment. Children living in these accommodations usually have complex needs, such as challenging behaviours, that can be exacerbated by an environment that is not suited for them (Socialstyrelsen, 2020). This master’s thesis aims to investigate how architecture can promote the wellbeing of children with ASD living in group accommodations. Furthermore, it investigates how these accommodations can be homelike and connect residents to nature. The thesis is in collaboration with Betaniahemmet, an organisation in Gothenburg municipality, and the aim is also to provide them with information and strategies that they can use in future projects. The research was conducted using a literature study, study visits, and interviews with staff, parents, and experts on group accommodations for children and ASD. The gathered information was then analysed and formulated into design strategies, a spatial program and spatial organisation that were implemented in the design of a group accommodation. The theory is based on literature about ASD, group accommodations for children and adults with disabilities, therapeutic spaces, homelike spaces, and connecting residents to nature. The results suggest that well-being can be promoted by designing an accommodation that suits the residents’ specific needs regarding hyper- or hypo-sensitivities, perception and navigation in the building, difficulties meeting others, safety, and privacy. A homelike feeling is created primarily by providing residents with a private space that they have control over and by choosing familiar materials to the extent that it is possible. To connect residents to nature, it is perhaps most important to provide a garden with various activities and create the possibility of having views and daylight in the building. It is, however, important that these forms of stimulation from the environment can be screened off
Keywords: Autism spectrum disorder | well-being | homelike | connection to nature